The worship of Confucius in Japan - McMullen, James (Harvard East Asian monographs, 2020)
"Provides the first overview of the richly documented and colorful Japanese version of the East Asian ritual to venerate Confucius, known in Japan as the sekiten. Traces the evolution of the sekiten in Japan from pre-modern times up to the present"--Provided by publisher